Working Towards Usability for Computer-based Māori Whakapapa Systems - Gill, Manjit Singh (Auckland University of Technology, 2006)
This thesis investigates the process of gathering user requirements for a computer system to support processes involved with Maori genealogy (whakapapa). The two main objectives are: 1). to provide information on users’ requirements, and 2). to assess and refine where needed the usability approach and techniques (usability instrument) for such a task. The applied research is informed by usability methods and is emergent in that the aim is to apply the best method for the task at hand, to reflect on outcomes and then do the next step. Initial interviews and some fine-grained analysis of data types from existing data were done. In-depth inquiry into actual users was seen to be needed to get a more detailed picture of not only the specific needs but also to put that into a wider perspective of users’ life values and goals. Several interviews were conducted. The usability ‘methods’ of building personas and user profiling were applied to the data but the end result did not reflect the breadth and difference in users. In-depth analysis of the interview data lead to identification of a number of crucial areas that require further research, importantly; how computer-based systems would enhance the learning relationship and get young people involved and how access, security and validity would be designed. The concept of Maori as a group user was proposed, which includes the roles of knowledge holder, technical expert and end user with each role using the system in a different, but cohesive, way. Further work needs to be done in investigating sub-groups within Maori not covered in this study; particularly young people and people living in rural areas. In summary, the research raised more questions than answers in terms of user requirements, however it did produce applied investigation of methods that can be used to progress the gathering of user requirements and providing a basis for usability.
Keywords: Maori (New Zealand people) -- Genealogy; System design; Whakapapa; Reo